1992
DOI: 10.1042/bj2860305
|View full text |Cite
|
Sign up to set email alerts
|

Eicosapentaenoic acid inhibits cell growth and triacylglycerol secretion in McA-RH7777 rat hepatoma cultures

Abstract: The plasma triacylglycerol-decreasing effect of fish-oil fatty acids was studied in vitro by using the rapidly growing cultured rat hepatoma cell line McA-RH7777. Cells were exposed to albumin-complexed eicosapentaenoic acid (C20:5n-3; EPA), to oleic acid (C18:1n-9; OA), or to albumin alone. Cell growth was similar in albumin- and OA-supplemented cultures, but EPA treatment inhibited growth. As estimated by [14C]glycerol incorporation, OA stimulated both net triacylglycerol synthesis and secretion over control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 73 publications
1
6
0
Order By: Relevance
“…There have been some investigations of the anticancer effect of EPA on hepatoma cell lines [34][35][36][37], implanted [38][39][40], and diethylnitrosamine-induced hepatoma [41]. In this context, our present study is the first to demonstrate that EPA inhibits HCC in steatohepatitis.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…There have been some investigations of the anticancer effect of EPA on hepatoma cell lines [34][35][36][37], implanted [38][39][40], and diethylnitrosamine-induced hepatoma [41]. In this context, our present study is the first to demonstrate that EPA inhibits HCC in steatohepatitis.…”
Section: Discussionmentioning
confidence: 53%
“…In this context, our present study is the first to demonstrate that EPA inhibits HCC in steatohepatitis. Previous studies revealed that the mechanism underlying the cytotoxicity of EPA to hepatoma cells was ascribed to either induction of cell death or inhibition of cell proliferation [34][35][36][37][38][39][40]. In 40-week-old Pten KO mice, EPA administration was not responsible for apoptosis but rather inhibiting proliferation of precancerous hepatocytes, as demonstrated by PCNA nuclear staining.…”
Section: Discussionmentioning
confidence: 95%
“…2B, while all three fatty acids increased secretion of labeled TG (compared with the results from incubation with BSA alone), the greatest increase was seen with OA ( ‫ف‬ 3 ϫ greater, P Ͻ 0.01). As reported by us and others (17,25), relative to the results with OA, incubation of McA cells with an n-3 fatty acid resulted in decreased secretion of labeled TG, but, surprisingly, so did incubation with MA ( P Ͻ 0.01 for either DHA or MA vs. OA). Because of this unexpected result, we wished to further explore the effects of MA that led to increased apoB-100 secretion and decreased TG secretion.…”
Section: Changes In Apob-100 Secretion Are Independent Of Induction Omentioning
confidence: 53%
“…Keler et al(1992) showed that dietary linoleic acid increases hepatoma growth. Fish oil was found to inhibit hepatic carcinogenesis (Ramesh and Das, 1995) and decrease growth (Fox and Hay, 1992). It is probable that this effect of linoleic acid is mediated through prostaglandin E2 (PGE2).…”
Section: Influence Of Liver Cancer On Fatty Acid Metabolismmentioning
confidence: 99%